Empirical Data as Content Substance of Theories - Meškauskas, Eugenijus (Problemos, 1979)
The article deals with the dialectical concept of the foundation of theories by factual evidence. It considers the dependence of the information yielded by factual data on fundamental theoretical prerequisites. It also deals with the question of qualitative difference of the experiment as contrasted with immediate observation of nature.